IMPLEMENTATION OF HALAL TRACEABILITY SUPPLY CHAIN WITH SUPPLY CHAIN OPERATION REFERENCE (SCOR) MODEL FOR HALAL FOOD INDUSTRY - Zahro Ubay Dilla; Muhamad Said Fathurohman (Jurnal Ekonomi Syariah Teori dan Terapan, 2021)
ABSTRAKTujuan dari penelitian ini adalah menggambarkan hasil implementasi dari sistem halal traceability supply chain pada produk makanan halal pengolahan daging di perusahaan Ternaknesia Farm Innovation. Analisis pada penelitian ini menggunakan model Supply Chain Operation Reference (SCOR) sebagai model utama dalam pengembangan halal traceability supply chain. Perusahaan ini tengah mengembangkan sistem jaminan ketelusurah halal (halal traceability supply chain) pada produk daging yang dijual nya dengan membuat model bisnis Ternaknesia 2.0 yang berkelanjutan sebagai perusahaan pertama di wilayah Surabaya Jawa Timur yang memiliki sistem halal traceability. Hasil identifikasi atas Implementasi dari halal traceability supply chain menunjukan bahwa penerapan sistem halal traceability di perusahaan mampu meminimalisir terjadinya ancaman kontaminasi zat haram yang ditelusuri dari implementasi pada proses model SCOR yaitu plan,resource,make, deliver return, dan enable dengan mengembangkan konsep halal dan thoyyib pada produk daging halal yang dijual. Teknologi yang digunakan dalam implementasi pelacakan proses ketertelusuran halal atau halal traceability system yaitu dengan penggunaan label QR Barcode Scan dan didukung penggunakan EPICS code pada produk daging halal yang dijual di perusahaan, sehingga memberikan jaminan ketelusuran halal rantai pasok kepada konsumen. Kata Kunci: halal traceability supply chain dan makanan halal. ABSTRACTThe purpose of this study is to describe the results of the implementation of the halal traceability supply chain system on halal food products for meat processing at the Ternaknesia Farm Innovation company. The analysis in this study uses the Supply Chain Operation Reference (SCOR) model as the main model in the development of halal traceability supply chain. The company is developing a halal traceability supply chain guarantee system for the meat products it sells by creating a sustainable Ternaknesia 2.0 business model as the first company in the Surabaya area of East Java to have a halal traceability system. The results of the identification of the implementation of the halal traceability supply chain show that the implementation of the halal traceability system in the company is able to minimize the threat of contamination of illicit substances traced from the implementation of the SCOR model process, namely plan, resource, make, deliver return, and enable by developing the concept of halal and thoyyib. on halal meat products sold. The technology used in the implementation of tracking the halal traceability system is the use of a QR Barcode Scan label and supported by the use of the EPICS code on halal meat products sold in the company, thus providing guarantees for supply chain halal traceability to consumers.Keywords: halal traceability supply chain and halal meat products.DAFTAR PUSTAKAGoods, I. C. (2013). MS 2200-2:2013 Islamic Consumers Goods Usage of animal bone, skin and hair - General guidelines.Harwati., & Pettalolo, A. N. Y. (2019). Halal criteria in supply chain operations reference (SCOR) for performance measurement: A case Study. IOP Conference Series: Materials Science and Engineering, 505(1). https://doi.org/10.1088/1757-899X/505/1/012020Heng, M. S. H., Fiedler, B., & Kandunias, C. (2005). Implications of supply chain management for accounting information systems. 9th Pacific Asia Conference on Information Systems: I.T. and Value Creation, PACIS 2005, 1037–1045.Hobbs, J. E. (2003). Consumer demand for traceability. International Agricultural Trade Research Consortium, 2003. Retrieved from http://www.iatrcweb.orgInsulation, T., & For, P. (2010). Malaysian standard buildings - Factory made mineral.International Standard Organization (ISO) 9001:2000. (2000). 3rd, 32.KNEKS. (2020). KNEKS dorong traceability produk halal dengan blockchain. Retrieved from https://knks.go.id/berita/267/kneks-dorong-traceability-produk-halal-dengan-blockchain?category=1Lambert, D. M., Cooper, M. C., & Pagh, J. D. (1998). Supply chain management: Implementation issues and research opportunities. The International Journal of Logistics Management, 9(2), 1–20. https://doi.org/10.1108/09574099810805807Leidecker, J. K., & Bruno, A. V. (1984). Identifying and using critical success factors. Long Range Planning, 17(1), 23–32. https://doi.org/10.1016/0024-6301(84)90163-8Lu, Q., Goh, M., & Souza, R. D. (2016). A SCOR framework to measure logistics performance of humanitarian organizations. Journal of Humanitarian Logistics and Supply Chain Management, 6(2), 222–239. https://doi.org/10.1108/JHLSCM-09-2015-0038Olhager, J. (2003). Strategic positioning of the order penetration point. International Journal of Production Economics, 85(3), 319–329. https://doi.org/10.1016/S0925-5273(03)00119-1Poniman, D., Purchase, S., & Sneddon, J. (2015). Traceability systems in the Western Australia halal food supply chain. Asia Pacific Journal of Marketing and Logistics, 27(2), 324–348. https://doi.org/10.1108/APJML-05-2014-0082Rashid, N. A., & Bojei, J. (2020). The relationship between halal traceability system adoption and environmental factors on halal food supply chain integrity in Malaysia. Journal of Islamic Marketing, 11(1), 117–142. https://doi.org/10.1108/JIMA-01-2018-0016Ringsberg, H. A., & Mirzabeiki, V. (2014). Effects on logistic operations from RFID- and EPCIS-enabled traceability. British Food Journal, 116(1), 104–124. https://doi.org/10.1108/BFJ-03-2012-0055Saifudin, A. M., Zainuddin, N., Elias, E. M., Samsuddin, S. N. F., & Osman, A. A. (2018). Reviewing the contributors towards the performance of the new Islamic supply chain model. International Journal of Supply Chain Management, 7(4), 151–157.Souprayen, B., Ayyanar, A., & K, S. J. (2021). Improvement of C5.0 algorithm using internet of things with Bayesian principles for food traceability systems. Modern Supply Chain Research and Applications, 3(1), 2–23. https://doi.org/10.1108/mscra-07-2020-0019Spens, K. M., Kovács, G., & Vellenga, D. B. (2004). Transportation and logistics networks in the baltic states: Keys for successful economic development and integration into the E.U. Ekonomika, 68, 121–134. https://doi.org/10.15388/ekon.2004.17401Supply Chain Operations Council. (2017). Supply chain operations reference model. In Logistics Information Management.Tieman, M., Van der Vorst, J. G. A. J., & Ghazali, M. C. (2012). Principles in halal supply chain management. Journal of Islamic Marketing, 3(3), 217–243. https://doi.org/10.1108/17590831211259727Zainuddin, N., Saifudin, A. M., Deraman, N., & Osman, A. A. (2020). The effect of halal traceability system on halal supply chain performance. International Journal of Supply Chain Management, 9(1), 490–498.